Confederate Florida : The Road to Olustee - Nulty, William H. (Book collections on Project MUSE., 1990)
At the end of 1863 the Federal forces in the Department of the South were tied up in siege operations against Charleston and Savannah, operations that showed little progress or promise. The commander of the Department, Major General Quincy A. Gillmore, led an expedition into Florida to recruit blacks, cut off commissary supplies headed for other parts of the Confederacy, and disrupt the railroad system within Florida. Expedition forces landed at Jacksonville on February 7, 1864. The engagement at Olustee, not far from Gainesville, took place on February 20, 1.